Policy diffusion, policy transfer, and policy mobilities revisited: A call for more interdisciplinary approaches in human geography - Wolfgang Haupt (Geography Compass, 2023)
Geographers and urban studies scholars tend to rely on policy mobilities approaches to explain processes of policy spread, whereas political scientists and public policy scholars usually draw on either policy diffusion or policy transfer. I challenge this widespread scholarly practice of selecting approaches based on the association with a certain discipline. Instead, first and foremost, the specific research aim(s) and question(s) should shape the choice of theoretical lens. Analytical or policy outcome-oriented studies should rely on policy diffusion and policy transfer, while a policy mobilities approach is best suited for more (policy) critical analysis. The approaches can also complement each other to a certain degree. Analytical and policy outcome-oriented approaches need a stronger critical perspective while policy mobilities scholars need to underpin their critique with constructive suggestions on how to improve established practices.
Keywords: 320; critical studies; policy diffusion; policy innovations; policy outcome-oriented studies; policy spread; policy transfer; urban policy mobilities